WORK SATISFACTION: PERCEPTION OF NURSES OF A UNIVERSITY HOSPITAL - Amanda Ceschini Rigue; Graziele de Lima Dalmolin; Katiane Sefrin Speroni; Julia Zancan Bresolin; Andreia Aldair Rigue (Universidade Federal do Paraná, 2016)
The aim of this study was to investigate the perceived work satisfaction of nurses in a hospital in southern Brazil. This quantitative study was conducted with 144 nurses of a university hospital, from December 2014 to February 2015, using the Index of Work Satisfaction. The results showed that 79.2% (n = 114) of the nurses reported having autonomy, however, 47.9% (n = 69) need to carry out activities that went against their better judgment in some situations. For 75.7% (n=109) the interaction with the nursing staff was satisfactory, while for 70.1% (n=101) the interaction with doctors was permeated by the devaluation of their work and knowledge. Regarding the salary, 79.2% (n=114) considered it satisfactory; 93.8% (n=135) considered their work important; 88.2% (n = 127) were satisfied with the work performed and 80.6% (n = 116) considered that bureaucratic activities hampered more qualified care. The importance is highlighted of the institutions evaluating the needs of professionals and seeking strategies to increase their satisfaction.